POLITICAL URBANISM: CHALLENGES AND PROSPECTS - Andrey P. Koshkin; Sergey A. Mel'kov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article focuses on the fact that when big cities come into being priorities in organization of real policy and political subjectivity are moving toward metropolises. Certain characteristics of increasing political subjectivity of metropolises in the 21st century were identified. Parameters of Russian cities, which form numerous agglomerations were determined. The authors stress that in our country the development of city agglomerations is an objective of the federal scale. The clearly observed trend of Russian political modernization by hierarchical system - from federal cities and cities with a million population to smaller cities and towns. The authors show the growing prospects and shaping the limits of political urbanization, such as changing role of city-dwellers in political life of society, the role of mass communications in political life of cities, specific features of forming power in Moscow, establishing values of liberal ideology and democracy in cities, appearance of political parties and public movements, rising interest of various political forces to political management, arising of 'orange', 'flower' and other types of revolutions in cities.